Bimbingan Teknis Amoniasi Jerami pada peternak sapi di Desa Wonua Kecamatan Konda Kabupaten Konawe Selatan - Bain, Ali; Has, Hamdan; Dzulkarnain, Deki (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2023)
Community service program providing technical guidance by the Halu Oleo University KKN-Thematic Team to the farmers. Implementation of activities carried out in Wonua Village, Konda District, South Konawe Regency. This activity aims to increase the knowledge and skills of farmers in processing rice straw as ruminant feed so that it can fulfill shortage of feed during the dry season. The method of implementing the activity begins with with a location survey in Wonua Village, analyzing the problems experienced and exploring the potential that exists in Wonua Village, implementing technical guidance, and evaluation of activities. Wonua farmer is given additional knowledge through the technical guidance activities of straw ammoniation so that they can maximize rice straw that has no previous useful value into ruminant feed. This activity involved the thematic KKN team from the faculty of animal husbandry UHO, students participating in KKN and also the farmers. This technical guidance has been able to provide additional knowledge for the community to independently process rice straw into ammoniated straw which is useful when there is a shortage of animal feed useful when there is a scarcity of ruminant feed.